PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2019) - Amelia, Amelia; Raja Adri, Surya Satriawan; Vera, Oktari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The purpose of this study was to determine the effect of Intellectual Capital on Firm Value With The Profitability As A Moderating Variable in manufacturing companies listed on the Indonesia Stock Exchange (BEI). The data used in this research is secondary data, namely the Annual Report. The population in this study are all manufacturing companies listed on the IDX for the 2017-2019 period. The number of samples in this study were 192 samples for 3 years using purposive sampling. The analysis technique in this study used moderated regression analysis (MRA) and was performed using SPSS version 25. The results of this study indicate that the Value Added Capital Employed (VACA) affects the firm value with significant values of 0,000, Structural Capital Value Added (STVA) does not affect the firm value with significant values of 0,517. Profitability has significant effect in mediating the relationship between VACA against Firm Value with significant values of 0,003, Profitability has significant effect in mediating the relationship between STVA against Firm Value with significant values of 0,003.Keywords: Firm Value, Intellectual Capital, VACA, STVA, Profitability